Pertumbuhan Stek Batang Tumbuhan Obat Tali Kuning (Tinospora dissitiflora Diels) Pada Media Tanah Dan Pasir - Yohanes Taam; Ana Tampang; Wahyudi Wahyudi (Median : Jurnal Ilmu Ilmu Eksakta, 2020)
Tali kuning (Tinospora dissitifloraÂ Diels) is medicinal plant endemic to New Guinea, widely used to prevent and cure malaria symptoms in Papua. In utilizing this plant, they harvest directly from the forest without planting. If this continue, it will become extinct. This research, therefore, is to investigate responds of cutting stem of Tali kuning planted on four media, soil, sand, and forest litter and their combinations. Variables consist of growing cuttings, callus cuttings, shoots cuttings, rooted cuttings and express in percent. The cuttings produce callus, shoots, and leaf are expressed in days. Numbers of leaf, roots, and tendrils (shoots enlengthen) are counted in sheets. Length of tendrils and roots are measured in cm. The results indicate that Tali kuning can be planted using cutting stem in the media tested. Soil media resulted the highest percentage of growing cuttings, callus, shoots, and rooted. Callus is produced at 16 days at average, shoots at 21 days, and leaf at 26 days. Each media produces a single tendril at average 27.44 cm in length, 15 roots with 5.84 cm long, and leaf of 8 sheets. Tukey test indicates that four planting media did not result significantly different for growth variable, except for the length of roots.Key words:Â Growth, cutting stem, Tali kuning, planting media